Factors Caused for Intra Natal Care and Postnatal Care at Home: Qualitative Study on the Location of Birth - Agustina Abuk Seran; Nurlaelah Al-Tadom; Adriana Boimau; Sherlyansie Boimau; Linda Risyati (Jurnal Keperawatan, 2022)
The safe motherhood program aims to strengthen maternal health efforts at regional and national levels in the context of equality, poverty reduction, and human rights. However, maternal mortality remains a major challenge for health systems worldwide. Maternal morbidity and mortality rates in the Province of East Nusa Tenggara (NTT) are still a problem because of complications during pregnancy or childbirth and there are stillbirths monitored and assisted by non-professionals at home. To increase and encourage the use of maternal health services, it is very important to understand the factors that influence maternal care-seeking behavior in NTT. This study was designed to explore societal values ​​and practices surrounding labor and the postpartum period, the influence of these values ​​and practices on health-seeking behavior, and the barriers and enabling factors to seek and utilizing maternal health services. We performed a rapid ethnographic assessment of maternal care-seeking behavior. It discusses local beliefs and practices related to childbirth and postpartum to determine the socio-cultural factors that contribute to the low absorption of maternal health services in NTT Province. This study seeks to identify and assess the factors that influence home delivery in Malacca District, NTT Province. This research is a qualitative research with an ethnographic approach. Data collection was carried out in April-August 2022 in Malacca Regency. Data were collected through in-depth interviews and FGDs with 30 informants, namely new mothers giving birth 0-3 months Thematic analysis of interview data and FGDs. Of the 30 cases submitted, 16 cases decided to give birth at a health care facility, 12 cases gave birth at home, 2 cases gave birth on the way to a health facility. Five dominant themes affecting the location of delivery were identified: the perception of normal delivery; motivation to encourage the provision of health facilities; home delivery and postpartum practices; decision-making process; and the level of knowledge about the danger signs of labor and postpartum.